The Effect of Bay Leaf (Syzygium polyanthum) Inclusion in the Egg Salting Process on Taste and Chemical Characteristics - Arifuddin; Prasetia, Muh Andika; Andi Iksan; Rini Anggriani (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This research aims to determine the effect of the use of bay leaves (Syzygium polyanthum) on organoleptic value and salt egg chemical content. The research design used was a complete randomized design of direct pattern with 4 treatments and 4 replications respectively. The treatments were without giving bay leaf (K0), giving 5% bay leaf (K1), giving 10% bay leaf (K2), giving 15% bay leaves (K3). Variable observed included organoleptic value (color, egg white consistency , aroma, flavor, fossils, whole), protein content, fat content and cholesterol content. The data were analyzed by variance analysis, if there were significant differences between treatments then tested further with Duncan's Multiple Range Test (DMRT). The eggs were used as many as 160 duck eggs were divided into 4 treatments of bay leaf repeated 4 times, each replication amounted to 10 eggs. The results of the research on the organoleptic tests, which included color, consistency of the egg white, aroma, taste, packaging, and overall quality, showed that treatments K0 and K3 had the same level of preference from the panelists. Meanwhile, treatment K3 was able to significantly increase protein content and reduce fat and cholesterol content compared to the control treatment (P<0.05). Based on the research results, it can be concluded that the 15% treatment is the best level for organoleptic tests and the chemical content of salted eggs.